Supply response of wheat in Bangladesh: cointegration and vector error correction analysis - A. S. M. Anwarul Huq,; Mohamed Arshad, Fatimah; Md Nurul Islam, Gazi (Academic Journals, 2013)
Numerous past studies on wheat cultivation in Bangladesh is criticized for using the weaker Nerlovian Partial Adjustment models and also for analytical interpretation through Ordinary Least Square (OLS) creating spurious results for time series data. This problem can be avoided if Econometric technique of co-integration is used. It is for this the present paper estimates the supply response of wheat in Bangladesh by using the modern technique of co-integration with Vector Error Correction Model (VECM). Our unit root analysis indicates that underlying data series were not stationary and are all integrated of order one, that is I(1). The Johansen multivariate co-integration approach indicates the presence of a co-integrating relationship in the supply response model. Wheat acreage is significantly influenced by price of wheat, and other competing crops such as Boro rice. The non-price factors weather has a highly positive effect on wheat area in the short-run. The wheat supply elasticity’s are found to be inelastic both in the short-and long-run. The long-run and short run price elasticity’s were 0.95 and 0.47, respectively.